Genotoxicity induced by endodontic sealers: A systematic review - Thiago Guedes Pinto; Ana Claudia Muniz Renno; Jean Nunes dos Santos; Patricia Ramos Cury; Daniel Araki Ribeiro (Saudi Dental Journal)
Introduction: This systematic review aimed to help further elucidate the following question: are endodontics sealers able to induce DNA damage in vitro or in vivo? Methods: This study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement 2020 criteria. A total of 23 studies were carefully selected by the authors. Results: Regarding the general characteristics, most studies evaluated, on average, 3–5 types of sealers (resin epoxy, salicylate, salicylate + MTA, zinc oxide-eugenol, bioceramic products, calcium hydroxide), performing comparisons between them. Our results demonstrate that endodontic sealers may be a genotoxic agent since most studies demonstrated positive findings, with the resin-based ones being the most potentially genotoxic. Conclusion: The type of genotoxicity assay, material evaluated, and dilution concentration levels influenced the outcome. This study clarifies whether and to what extent endodontic sealers are capable of inducing DNA injury in oral tissues.